MFEP-Based Evaluation of Public Information Governance with Socio-Technical and Data Lifecycle Perspectives - Retnowati, Retnowati; Eko Nur Wahyudi; Purwatiningtyas (Information Technology International Journal, 2025)
In the era of public information disclosure, public information management is essential for transparency, accountability, and citizen participation. This study assesses eight Public Information Management Officers (PPID) in Central Java, Indonesia, utilizing 21 variables measured by a Multi-Factor Evaluation Process (MFEP) based on Data Lifecycle Management (DLM) and Socio-Technical Systems (STS). Data was collected using Likert-scale questionnaires, and performance was assessed using Evaluation Weight Value (EWV) and Total Evaluation Weight (TEW). The results suggest that technology-related indicators outperformed human competency and regulatory compliance. "Use" and "Disposal" were the DLM phases with the worst performance, demonstrating deficiencies in data accountability and infrastructure. In STS, the "People" dimension lagged, emphasizing the need for capacity building. The findings indicate that, while digital infrastructure is robust, governance and human resource development require strengthening. Strategic improvements in underperforming sectors are suggested to strengthen public information governance.